Glucose values from the same continuous glucose monitoring sensor significantly differ among readers with different generations of algorithm - Babaya, Naru; Noso, Shinsuke; Hiromine, Yoshihisa; Taketomo, Yasunori; Niwano, Fumimaru; Yoshida, Sawa; Yasutake, Sara; Kawabata, Yumiko; Maeda, Norikazu; Ikegami, Hiroshi (Scientific reports, 2024)
Continuous glucose monitoring (CGM) values obtained from CGM systems using the same sensor but with different internal algorithms (the first- and third-generation FreeStyle Libre (1st-gen-libre and 3rd-gen-libre, respectively)) were compared. We used 19,819 paired and simultaneously measured CGM values of 13 patients with diabetes. The average CGM value was significantly higher ( P < 0.0001) and the time below range (CGM value < 70 mg/dL) was significantly lower ( P < 0.0001) with the 3rd-gen-libre than with the 1st-gen-libre. There was a significant correlation ( P < 0.0001) between the CGM values of the 3rd-gen-libre (y-axis, mg/dL) and 1st-gen-libre (x-axis, mg/dL) using the following formula: y = 0.9728x + 10.024. On assessing the association between glycated hemoglobin (HbA1c (%), y-axis) and the average CGM values (x-axis, mg/dL) by applying the obtained equation to previously reported 1st-gen-libre data and converting it to 3rd-gen-libre data, we obtained the equation y = 0.02628x + 3.233, indicating that the glucose management indicator reported in the West may be underestimated compared with the laboratory-measured HbA1c in the Japanese population. Glucose values from the same sensor were found to be significantly different between readers with different algorithms, and the calculation of CGM-related indices may need to be individualized for each device.